AN ANALYSIS OF THE SLANG LANGUAGE USED IN THE MOVIE “JUNO” - Cynantia Rachmijati (STKIP Siliwangi, 2015)
This research entitled “An Analysis of the Slang Language used in the movie Juno” is a descriptive analysis of how slang language is used among youngster from the movie entitled “Juno”. The objective of the research is to analyze the slang language and to see whether “Juno” can be used as teaching materials. The research method is descriptive analysis to analyze the slang languages and utterances that found from the movie. The amount of slang utterances that found in this movie are : Juno has 38 lines, Mac has 8 lines, Bren has 7 lines, Mark has 6 lines, Vanessa has 2 lines, Leah has 5 lines, Paul has 3 lines and other supporting roles has 5 lines– which makes the total of 73 slang utterances. It is concluded that “Juno” is suitable as teaching materials, especially for ESL who are interested in studying slang.Keywords : analysis, slang, language, movie